Haptic feedback in a virtual crowd scenario improves the emotional response - Venkatesan, R. K.; Banakou, Domna; Slater, Mel; M., Manivannan (Frontiers in Virtual Reality, 2023)
Research has shown that incorporating haptics into virtual environments can increase sensory fidelity and provide powerful and immersive experiences. However, current studies on haptics in virtual interactions primarily focus on one-on-one scenarios, whilst kinesthetic haptic interactions in large virtual gatherings are underexplored. This study aims to investigate the impact of kinesthetic haptics on eliciting emotional responses within crowded virtual reality (VR) scenarios. Specifically, we examine how the type or quality of the haptic feedback influences the perception of positive and negative emotions. We designed and developed different combinations of tactile and torque feedback devices and evaluated their effect on emotional responses. To achieve this, we explored different combinations of haptic feedback devices, including “No Haptic”, “Tactile Stimulus” delivering tactile cues and “Haptic Stimulus” delivering tactile and torque cues, in combination with two immersive 360o video crowd scenarios, namely “Casual Crowd” and “Aggressive Crowd”. Results suggest that varying the type or quality of haptic feedback can evoke different emotional responses in crowded VR scenarios. Participants reported increased level of nervousness with Haptic Stimulus in both virtual scenarios, whilst both Tactile Stimulus and Haptic Stimulus were negatively associated with pleasantness and comfort during the interaction. Additionally, we observed that participants’ sense of the touch being real was enhanced in Haptic Stimulus compared to Tactile Stimulus. The “Haptic Stimulus” condition had the most positive influence on participants’ sense of identification with the crowd.